Discovery and characterization of ligase activity determinants in plant asparaginyl endopeptidases - Chan, Ning-Yu (Nanyang Technological University, 2022)
Ligases are important protein catalysts. A small group of the ligases is ATP- independent, requires no cofactors, and functions in physiological conditions. These ligases are versatile biochemical tools. Asparaginyl endopeptidases (AEPs) are cysteine proteases that break Asn/Asp(Asx)-peptide bonds. Recently, a small group of AEPs is found to function as peptide asparaginyl ligases (PALs). The discovery of PALs with diverse substrate preferences expands the repertoire of enzyme-mediated ligation methods. However, PALs and protease AEPs are similar, making it challenging to identify PALs in a sea of AEPs. In this thesis, my goal is to identify and engineer novel PALs from the dataset using the sequence motifs, ligase activity determinants. The proposed study simplifies the process of searching novel PALs, and could yield new insights into the ligase activity of PALs. My results expand the catalog of PALs and pave the way toward the understanding of the molecular basis underpinning the ligase activity.